Three-year experience of prophylactic placement of inferior vena cava filters in women with gynecological cancer - Babu, Suresh B (Dove Medical Press, 2013)
OBJECTIVE: To evaluate the outcomes of prophylactic placement of inferior vena cava (IVC) filters to prevent pulmonary embolism (PE) in women undergoing surgery and chemotherapy for gynecological cancer. METHODS AND MATERIALS: Thirty-eight IVC filters were placed in 38 women between January 2008 and January 2010; 25 of these were placed in gynecological cancer patients for prevention of PE during surgery and the postoperative period. The patients’ electronic medical records, follow-up computed tomography scans, and outpatient follow-up notes were retrospectively reviewed for incidence of PE and adverse events. RESULTS: After 6 months of follow-up, no PE was observed and there was no mortality. Nine filters were retrieved uneventfully, and there were no clinical complications associated with any indwelling filter. CONCLUSION: IVC filters are safe and beneficial towards preventing PE in women undergoing surgery and chemotherapy for gynecological cancer.